2023
DOI: 10.1192/bjo.2023.545
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family interventions on communication in the context of anxiety and depression in those aged 14–24 years: systematic review of randomised control trials

Alex Lloyd,
Amy Broadbent,
Edmund Brooks
et al.

Abstract: Background The ability to communicate is integral to all human relationships. Previous research has specifically highlighted communication within families as both a risk and protective factor for anxiety disorders and/or depression. Yet, there is limited understanding about whether communication is amenable to intervention in the context of adolescent psychopathology, and whether doing so improves outcomes. Aims The aim of this systematic review was to determine in which contexts and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The findings showed that certain communication styles, especially passive and aggressive ones carried out by parents towards adolescents, were positively correlated with poor attachment, fear and distrust of others, and neglect of the environment (Maximo, 2011). The same thing is reinforced by findings explaining that parental communication affects children in managing anxiety and finding various alternative solutions so that children do not develop behavior that does not deviate due to the problems faced (Lloyd et al, 2023;Halimah et al, 2020). Vice versa, communication can also have a positive impact, such as openness between children and parents, trust, and attachment in the relationship between children and parents so that children are encouraged to openly tell about the conditions they are experiencing (Fasakin, 2017).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The findings showed that certain communication styles, especially passive and aggressive ones carried out by parents towards adolescents, were positively correlated with poor attachment, fear and distrust of others, and neglect of the environment (Maximo, 2011). The same thing is reinforced by findings explaining that parental communication affects children in managing anxiety and finding various alternative solutions so that children do not develop behavior that does not deviate due to the problems faced (Lloyd et al, 2023;Halimah et al, 2020). Vice versa, communication can also have a positive impact, such as openness between children and parents, trust, and attachment in the relationship between children and parents so that children are encouraged to openly tell about the conditions they are experiencing (Fasakin, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, adolescents need guidance or direction from parents to face various difficulties; one way is through maintaining good communication (Polcari et al, 2014). Adolescents need guidance from their families while facing various difficulties in the form of social support (Lloyd et al, 2023;Majid et al, 2023). Through good communication, parents can encourage adolescents to behave in a good manner.…”
Section: Introductionmentioning
confidence: 99%